2004
DOI: 10.1111/j.1463-1326.2004.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of programme adherence and weight loss in women in an obesity programme using meal replacements

Abstract: Objective: To explore predictors of programme adherence and weight loss in patients participating in a weight management programme using meal replacements (MR).Design: 150 healthy obese women, age 48.5(sd=8.3) years; weight, 97.6(13.4) kg; BMI 36.5(3.7), participated in a longitudinal study with a 16-week acute weight loss phase (Phase 1) followed by one year of a trial of weight loss maintenance (Phase 2). Energy intake during Phase 1 totaled 900 kcal (3.7MJ) a day from a diet including two meal replacements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 25 publications
5
47
2
Order By: Relevance
“…Several researchers have previously demonstrated that initial weight loss is associated with study dropout in dietary based weight loss trials [9][10][11][12][13][14][15][16] , however this finding is not consistent and others have found no relationship 11,17,18 . This is the first study to quantify the amount of initial weight loss which predicts dropout and to investigate and quantify additional easily obtainable subject characteristics such as age which can be used to ensure adequate randomisation.…”
Section: Discussioncontrasting
confidence: 46%
“…Several researchers have previously demonstrated that initial weight loss is associated with study dropout in dietary based weight loss trials [9][10][11][12][13][14][15][16] , however this finding is not consistent and others have found no relationship 11,17,18 . This is the first study to quantify the amount of initial weight loss which predicts dropout and to investigate and quantify additional easily obtainable subject characteristics such as age which can be used to ensure adequate randomisation.…”
Section: Discussioncontrasting
confidence: 46%
“…Although obesity is recognized as a risk factor for insulin resistance (IR) for many mammals, including horses and ponies (Packianathan et al, 2005;Frank et al, 2006), the relationship between IR and the propensity to lose weight during DR has not previously been reported for Equidae. For man, evidence linking IR to a propensity for weight gain or loss has largely been based on the retrospective analysis of observational data and reports are contradictory (Swinburn et al, 1991;Odeleye et al, 1997;Zavaroni et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…Rates of weight loss of $1% of outset BM weekly are considered clinically useful for man and companion animal species (Packianathan et al, 2005;German et al, 2007). Obtaining comparable rates of weight loss in obese ponies of Native breeds, has required relatively severe restriction of forage intake (Welsh Mountain ponies, 1% of BM as daily DMI, $67% of estimated maintenance digestible energy requirements [mDER]; Dugdale et al, 2010; Shetland ponies, $51% of mDER; van Weyenberg et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that weight loss in the beginning of a weight reduction program is an important determinant of further weight loss. [33][34][35] This could also be due to metabolic determinants. 36 The results indicate that the loss of fat-free mass was greater in the diet groups receiving fish.…”
Section: Discussionmentioning
confidence: 99%